Diseño e implementación de un sistema automático mediante controladores lógicos programables, para el montacargas (ASCENSOR) del Hospital provincial Julius Doepfner de Zamora Chinchipe. - Castillo Zhingre, Jefferson Miguel (2014)
This project of thesis focuses on the "DESIGN AND IMPLEMENTATION OF AN AUTOMATIC SYSTEM TROUGTH PROGRAMMABLE LOGIC CONTROLLERS FOR THE FORKLIFT ( LIFT ) OF JULIUS DOEPFNER PROVINCIAL HOSPITAL OF ZAMORA CHINCHIPE " in order to improve the operation and safety of the elevator ( lift) which connects two floors, ground floor and first floor. The importance of this research project is based on the approach of an innovation from the point of view of automation to optimize resources without neglecting the required technical and quality results. During the research process it was possible to evaluate and identify the lack of devices, such us electrical and electronic that helps an efficient and safe to transport users occupying the forklift operation. Implementation of the new automatic control system consists of the power circuit and control circuit automatic of maneuvers, these circuits are installed with the previously selected items. The automatic control of the forklift was made by using a PLC EASY which was selected according to the needs and conditions of operation. The program that controls the lift is designed so that start up, check the positioning of the car and especially being in control of the security system